ACTR-09. A PHASE 0 PHARMACODYNAMIC AND PHARMACOKINETIC STUDY OF EVEROLIMUS IN VESTIBULAR SCHWANNOMA (VS) AND MENINGIOMA PATIENTS. (11th November 2019) - Karajannis, Matthias; Goldberg, Judith; Thomas Roland, J; Sen, Chandranath; Placantonakis, Dimitris; Golfinos, John; Allen, Jeffrey; Dunbar, Erin; Plotkin, Scott; Akshintala, Srivandana; Schneider, Robert; Deng, Jingjing; et al.
Abstract: BACKGROUND: Inhibition of mTORC1 signaling has been shown to diminish growth of NF2 deficient tumors in preclinical studies, and clinical data suggest that everolimus, an orally administered mTORC1 inhibitor, may slow tumor progression in a subset of adult and pediatric NF2 patients with VS. To assess the pharmacokinetics, pharmacodynamics and potential mechanisms of treatment resistance, we performed a pre-surgical ("phase 0") clinical trial of everolimus in patients undergoing surgery for VS or meningiomas. METHODS: Eligible patients with meningioma or VS requiring tumor resection received everolimus 10 mg daily for 10 days immediately prior to surgery. Everolimus blood levels were determined immediately prior to and after surgery. Tumor samples were collected intraoperatively. RESULTS: Ten patients completed protocol therapy, including 5 patients with NF2-related meningioma, 3 patients with sporadic meningioma, and 2 patients with NF2-related VS. Median pre- and post-operative plasma levels of everolimus were found to be in a high therapeutic range (17.4 ng/ml and 9.4 ng/ml, respectively). Median tumor tissue drug concentration determined by mass spectrometry was 24.3 ng/g (range 9.2–169.2), and median tumor tissue to post-operative plasma drug concentration ratio was 0.39. We observed only partial inhibition of phospho-S6 in the treated tumors, indicating incomplete target inhibition compared to matched control tissues from untreated patients (p = 0.005). Consistent with prior observations that inhibition of mTORC1 may lead to MAPK pathway activation through a PI3K-dependent feedback loop, we observed a statistically significant increase of phospho-ERK (p < 0.03) versus untreated controls. CONCLUSIONS: In patients with meningioma or VS, treatment with everolimus leads to incomplete inhibition of mTORC1 signaling and upregulation phospho-ERK. These data may explain the limited anti-tumor effect of everolimus observed in clinical studies for NF2 patients and identify upregulation of phospho-ERK as a likely resistance mechanism that could be addressed with combination therapies.